Vyse vs. the Sisters of St. Joseph and Sweeney- A case of a retained eye needle - Rozovsky, Lorne; Rozovsky, Fay (Operating Room Nurses Association of Canada Journal, 1991)
On July 10, 1981 Dr. John P. Sweeney operated on the left inguinal hernia of Mark Vyse at St. Joseph’s Hospital in London, Ontario. Following the first phase of the operation a needle count was conducted. It was found that an eyed needle was missing and a hunt was commenced. Clothing, including hats and masks, drapes and ﬂoori ngwere checked as well as the site of the wound. No trace could be found.